External networking, leadership style and innovation on organizational performance in Malaysian construction industry / Megat Zuhairy Megat Tajuddin - Megat Tajuddin, Megat Zuhairy (2015)
This study aims to investigate the factors influencing organizational performance through innovation in construction industry in Malaysia. External networking (EN) and leadership style (LS) were identified as the determinants for innovation (IN) and organizational performance (OP) in this study. EN links various parties in project implementation in the form of inter-organizational collaboration and appropriate LS adopted by managers are capable in bringing industry players to work together as a team, reducing the adversarial relationships among them for greater performance. While EN facilitates in establishing the channel for information and resource flows, managers influence their subordinates to pursue ambitious goals through innovative efforts. EN brings together a project team to innovate and leaders who encourage their subordinates to be innovative will effectively lead to greater performance. These indicatively explain the potential role of IN in mediating the relationship between the two determinants and OP. The Diffusion of Innovation Theory by Rogers (2003) is identified as the underpinning theory of this study. The nature of the study is based on hypothesis testing in a cross sectional setting. Contractors and consulting companies were the population frame and were captured from the list provided by the industry's professional and regulatory bodies in Malaysia. A sample of 378 organizations was selected based on a stratified sampling method to grasp the sufficient representation of the different groups in the population. Regression analysis was performed to assess the hypothesized relationships between the identified variables. The results revealed six hypotheses are partially supported and one is rejected. EN and LS are identified significant in influencing both IN and OP. Nevertheless, not all dimensions of both variables support these outcomes. This result also supports the positive mediating role of IN in the relationship between LS and OP but not in mediating the EN and OP relationship. Theoretically, this study supports the needs for communication channels in a social system for innovation to diffuse. However, the finding implies the channel established through short-term relationship in the form of networking among project players in a project team, is not sufficient in influencing IN in the construction industry. Practically, the study implies construction managers are required to possess different styles of leadership in leading a project team and in leading an organization.